The potential role of DNA methylation in the pathogenesis of abdominal aortic aneurysm. Issue 1 (July 2015) - Toghill, Bradley J.; Saratzis, Athanasios; Harrison, Seamus C.; Verissimo, Ana R.; Mallon, Eamonn B.; Bown, Matthew J.
Abstract: Abdominal aortic aneurysm (AAA) is characterised by the chronic degradation and gradual, irreversible dilation of the abdominal aorta. Smoking, genetics, male sex and increased age are major factors associated with developing AAA. Rupture contributes to around 2% of deaths in all Caucasians over 65, and there is no pharmaco-therapeutic treatment. Methylation is an epigenetic modification to DNA, where a methyl group is added to a cytosine base 5′ to a guanine (CpG dinucleotide). Methylation patterns are long term, inherited signatures that can induce changes in gene transcription, and can be affected by both genetic and environmental factors. Methylation changes are involved in hypertension and atherosclerosis, both of which are risk factors of, and often coexist with AAA. Extra-cellular matrix degradation and inflammation, both important pathological hallmarks of AAA, are also promoted by changes in CpG methylation in other diseases. Additionally, the adverse effects of smoking and ageing take place largely through epigenetic manipulation of the genome. Every factor associated with AAA appears to be associated with DNA methylation, yet no direct evidence confirms this. Future work to identify a link between global methylation and AAA, and differentially methylated regions may reveal valuable insight. The identification of a common epigenetic switching process may also signify a promising future for AAA pharmaco-therapeutic strategies. Epigenetic therapies are being designed to target pathogenic CpG methylation changes in other diseases, and it is feasible that these therapies may also be applicable to AAA in the future. Highlights: AAA is a chronic degenerative disease of the aorta with several risk factors. Genetic studies have identified multiple loci that increase disease susceptibility. Changes in DNA methylation status are associated with every major hallmark of AAA. Hallmarks include proteolysis, inflammation, vascular cell death, smoking and ageing. There is no conclusive evidence of this link and future research is recommended.